Identification of Several Unique, Low-Molecular-Weight Basic Proteins in Dormant Spores of Clostridium bifermentans and Their Degradation During Spore Germination - Setlow, Peter (1976)
Two acid-soluble, low-molecular-weight basic proteins comprise ∼20% of the protein in dormant spores of Clostridium bifermentans. Both of these proteins are rapidly degraded during spore germination.